Structure-Activity Relationship Studies in Drug Development by NMR Spectroscopy - Atta-ur-Rahman; Iqbal Choudhary, M. (Bentham Science Publishers, 2011)
Drug discovery is still a process which involves screening of a large number of chemical compounds against a defined biological target. However, this approach is now being gradually replaced by more rational and knowledge-based approaches, such as in sillico screening and target based drug development. Increase in the cost of development of NME (New Molecular Entities) and productivity crises in pharmaceutical industry are catalyzing this change.Spectacular advances in the field of use of NMR spectroscopy in drug discovery and development have been triggered by a greater understanding of the disease process at the molecular level.While NMR is generally valued as an important tool for structure determination and more recently as a non-invasive diagnostic technique, its potential in drug discovery is based on its capacity to map molecular interactions at the atomic level. Chemical shifts, cross relaxation, and exchange of protons are among the NMR parameters which are highly sensitive to the exact molecular environments , and therefore yield information about how a small molecule (candidate compound) binds to a target protein (receptor) or to other macromolecules. These NMR parameters are also used to exactly map the part of the macromolecular target to which the ligand is bound. As a result, NMR is now extensively used as an efficient tool in the drug (ligand) discovery and optimization process or for the assessment of target drug ability. Recent advances in NMR hardware and methodology have provided a fresh impetus in the area of pharmaceutical innovation and productivity. This book is aimed to present recent cutting edge knowledge, practices and experiences in this important field.The book comprises seven scholarly written articles . Mailavaram and Devarakonda in their introductory review skillfully summarize the broad approaches of NMR-based drug discovery . Park and Kim focus on the use of NMR spectroscopic techniques in the study of drug delivery, drug release and other pharmaceutic parameters. Roberto and Marina provide a chronological account of fragment-based drug discovery by using NMR-based screening methods. Specific utilization of NMR-based techniques in the discovery and development of anticancer drugs is reviewed by Solomon and Lee. Ramalho et al. review another fascinating application of NMR in understanding the behavior and radio sensitizing properties of bioreductive drugs. Zoppetti comprehensively reviews the application of NMR spectroscopy in the study of host-guest cyclodextrin complexes, particularly their use as drug delivery vehicles. A concise review is contributed by Nhat and Hong on recent advances in the field of application of NMR in structure-activity relationship study of nanostructure drugs. These contributions of outstanding group of experts make this a very useful treatise of highly readable articles. Our felicitations and gratitude goes to them. The book will hopefully fulfill an important need of the scientific community by providing comprehensive reviews on cutting edge topics written by leading experts in the field.We extend our warmest thanks to the staff of Bentham Science Publishers, particularly, to Mr. Mahmood Alam (Director), Ms. Taqdees Malik (Editorial Assistant) and Ms. Sadaf Idrees Khan (Composer) for undertaking the important task of closely coordinating with the contributors and preparing the content lists, index, etc.